Religious Moderation and Diversity Management in Maintaning The Existence of The Brahmaraja Triloka Pura Community - Metta Puspita Dewi; Lery Prasetyo; Sutrisno Sutrisno (Hasanuddin University, 2022)
The Brahmaraja Triloka Pura Community is a group of individuals who can maintain their existence amidst the issue of intolerance. The members identify themselves as Shiva Buddha adherents. The members of the Triloka Pura Brahmaraja Community believe themselves to be the descendants of the last Majapahit. They have temples as a form of the ancestral tomb located in Ponggok District, Blitar Regency. The inauguration of the Brahmaraja Triloka Pura temple was attended by adherents of Islam, Hinduism, Buddhism, Catholicism, and Confucianism. Moderation of religion is reflected through tolerance, acceptance, and respect for the members' beliefs. There are even several types of places of worship in one temple complex such as the Brahma Caturmuka and kelenteng. Surface-level diversity lies in social status, age, gender, ethnicity, and religion. The deep level of diversity lies in the values, ideologies, and motives of each member in conducting worship at the temple. Diversity management which is applied through religious moderation maintains harmonious relations with all creatures, even the invisible ones, anti-discrimination, and orientation to the homogeneity of Majapahit descent from a blend of Javanese, Balinese, and Chinese.